2015
DOI: 10.1007/s00426-015-0691-8
|View full text |Cite
|
Sign up to set email alerts
|

Inducing attention not to blink: auditory entrainment improves conscious visual processing

Abstract: Our ability to allocate attention at different moments in time can sometimes fail to select stimuli occurring in close succession, preventing visual information from reaching awareness. This so-called attentional blink (AB) occurs when the second of two targets (T2) is presented closely after the first (T1) in a rapid serial visual presentation (RSVP). We hypothesized that entrainment to a rhythmic stream of stimuli-before visual targets appear-would reduce the AB. Experiment 1 tested the effect of auditory en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(45 citation statements)
references
References 65 publications
2
20
1
Order By: Relevance
“…The authors suggested that a more diffuse attentional state causes better T2 detection rates, either via arousal or via positive affective state (see also Olivers and Nieuwenhuis, 2006 ). Ronconi et al ( 2015 ) also found reduced AB effects when an auditory (but not when a visual) rhythm preceded the RSVP stream in the same frequency as the RSVP items. In general, however, there are also single reports, that the effect of music could not be replicated (Spalek and Di Lollo, unpublished data, as cited by Colzato et al, 2014 ).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…The authors suggested that a more diffuse attentional state causes better T2 detection rates, either via arousal or via positive affective state (see also Olivers and Nieuwenhuis, 2006 ). Ronconi et al ( 2015 ) also found reduced AB effects when an auditory (but not when a visual) rhythm preceded the RSVP stream in the same frequency as the RSVP items. In general, however, there are also single reports, that the effect of music could not be replicated (Spalek and Di Lollo, unpublished data, as cited by Colzato et al, 2014 ).…”
Section: Discussionmentioning
confidence: 95%
“…The authors argue that for stimuli presented with a frequency of about 10 Hz (i.e., approximately like the alpha frequency) those processes that underlie the generation of the P1 of the visual event related potential in the EEG (and that are related to alpha) interfere with those processes that enable the encoding of stimuli, specifically of T2. Second, there is recent work by Ronconi et al ( 2015 ) who studied the influence of an acoustic or visual rhythmic stream before the RSVP stream, but with the same frequency. The authors presented entraining stimuli before the RSVP stream either with a regular rhythm, that is with the same frequency as the RSVP stimuli, or with an irregular rhythm, that is with variable interstimulus intervals between the entraining stimuli.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alerting and orienting are the two main processes involved in reading acquisition.Alerting is defined as the multisensory attentional process that increases performance during tasks (Petersen & Posner, 2012), producing a phasic change in alertness (e.g., Ronconi, Pincham, Szűcs & Facoetti, 2016). The alerting system can be already measured in infant brain (e.g., .Attention orienting is the ability to select a spatial location (Petersen & Posner, 2012) or time event (Battelli, Pascual-Leone, & Cavanagh, 2007, for a review) inside the sensory field.…”
Section: Introductionmentioning
confidence: 99%
“…Attention orienting is described as a spotlight that moves to the attended area (Carrasco, 2011). The attention spotlight is not only oriented in a specific spatiotemporal location, but can also be adjusted in its size (i.e.,zoom-in and zoom-out of focusing attention, e.g., Facoetti, Lorusso, Paganoni, Umiltà, & Mascetti, 2003;Facoetti & Molteni, 2000;Facoetti, Paganoni, Turatto, Marzola, & Mascetti, 2000;Ronconi, Gori, Ruffino, Molteni, & Facoetti, 2013;Ronconi et al, 2016). Frontal and parietal areas are the neural substrate of the orienting and focusing of attention (Battelli et al, 2007;Corbetta & Shulman, 2002;Ronconi, Basso, Gori, &Facoetti, 2014).Subcortical lateral geniculate nucleus (LGN) and the pulvinar, in the thalamus has also been shown to participate in attentional orienting (Schneider & Kastner, 2009).…”
Section: Introductionmentioning
confidence: 99%